PENGARUH PEMBELAJARAN MATEMATIKA BERBANTUAN MEDIA VIDEO PEMBELAJARAN BERBASIS STEAM TERHADAP KEMAMPUAN LITERASI NUMERASI SISWA KELAS V SD NEGERI 01 KEPAHIANG - Agusdianita, Neza; Yusnia, Yusnia; Melisa, Melisa (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2024)
This research aims to determine the effect of mathematics learning assisted by STEAM-based video media on students' numeracy literacy abilities. Researchers used a quasi-experimental method (Quasy Experiment) which is quantitative research. Students in class V A and B at SDN Negeri 1 Kepahiang were the samples in this research. The technique used in this research was a pre-test and post-test which were designed in the form of essay questions, each consisting of 5 questions. The results of this research showed, in the pre-test the students in the experimental class obtained the highest score of 70 and the lowest score of 20 with an average of 44.5, while in the control class the highest score of 60 was obtained and the lowest score was 30 with an average of 39. Then the results of the normality test showed both samples were normally distributed, and the homogeneity test results were in homogeneous variants. Furthermore, in the post-test, the experimental class obtained a score of 72.5 and the control class obtained a score of 56 with an average score difference of 16.5. there is an influence from the use of STEAM-based learning video media on the numeracy literacy skills of students in the VA and VB classes of SD Negeri 01 Kepahiang.